Potential Prospects of Blockchain Technology for Government Data Security Transparency - Mukmin, M; Effendi, Ghina Nabilah; Sagala, Irmawati; Da Silva, Dulce Martins (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2026)
In today’s digital era, data security and transparency are crucial in various aspects of life. Blockchain technology provides an effective solution to improve data security and transparency. Blockchain technology offers a solution by providing a secure and reliable information system. Blockchain technology can guarantee the integrity and validity of stored data. This can be achieved by storing data in secure blocks and encrypting it to protect privacy. Furthermore, the decentralized blockchain technology system makes it difficult for untrained individuals to implement or disrupt. The application of blockchain technology to information security systems occurs in various industries, including banking, trade, and government. As a result, the rate of adoption of blockchain technology in Indonesia requires the involvement of all stakeholders. Further research and development are needed to maximize the potential of blockchain technology and accelerate Indonesia’s digital transformation. This study uses a qualitative, literature-based approach with Big Data Online. Data is analyzed with Vosviewer, which allows us to visualize and analyze networks and clusters of complex data. By using VOSviewer to explore the relationship between various elements of the dataset, keywords, documents, or even researchers, VOSviewer becomes a software to analyze and visualize the relationship network between various elements in bibliometric data. According to this study, blockchain can improve data security by encrypting data and creating irreversible transactional data. In addition, blockchain technology can improve data transparency by making all transactions within the system transparent and accessible to all parties.